The urgency of the existence of a storage house for state confiscated items in the military court environment - Muhammad Tri Hakbari (Goodwood Publishing, 2024)
Purpose: The Storage House for Confiscated State Goods (Rupbasan) within the Military Court environment is regulated in Article 93 paragraph (1) of Law Number 31 of 1997 concerning Military Courts, which furthermore delegates the TNI Commander to issue a Decree of the TNI Commander regulating Rupbasan within the Military Court environment, but in reality 27 years have passed since this law came into effect until now the Rupbasan within the Military Court environment has not been felt to exist because there has been no Decree of the TNI Commander regulating Rupbasan. This is urgent because Rupbasan is a place designated by law for the storage of confiscated state goods and state looted goods with the aim that these goods are stored properly during the ongoing legal process and can be used as evidence or returned to their owners after the completion of the legal process based on a court decision. Research Methodology: This research is a normative legal research using comparative law at the Ministry of Law and Human Rights (Kemenkumham) and the Corruption Eradication Commission (KPK). Conclusions: The conclusion of this study is that there is no specific regulation governing the Rupbasan in the Military Court environment. The absence of this regulation creates a legal vacuum that has an impact on the management of evidence in the Military Court environment which is still carried out by the ranks of the Oditurat. Compared to the Rupbasan under the Ministry of Law and Human Rights and the Corruption Eradication Commission, the Military Court appears to be lagging behind in terms of the regulation and implementation of the Rupbasan. The management of confiscated objects in the Ministry of Law and Human Rights and the Corruption Eradication Commission has been regulated in detail through various regulations and standard operating procedures, while the Military Court still faces legal uncertainty in the management of confiscated objects. The creation of legal products in the TNI environment must be guided by the TNI Commander Regulation Number 43 of 2015 concerning the Formation of Legal Products in the Indonesian National Army Environment as amended by the TNI Commander Regulation Number 48 of 2018 concerning Amendments to the Regulation of the Indonesian National Army Commander Number 43 of 2015 concerning the Formation of Legal Products in the National Army Environment.